Orphans and other vulnerable children in Tanzanian care institutions: Experiences of maltreatment and mental health problems - Getrude Mkinga; Anette Kirika; Tobias Hecker; Katharin Hermenau (Child Protection and Practice)
Background: Orphans and vulnerable children (OVC) are likely to have multiple experiences of maltreatment by different perpetrators in and out of institutional care. Child maltreatment has been shown to have serious and long-lasting consequences for children's development. Objectives: This study aims at examining maltreatment experiences of OVC in institutional care facilities in Tanzania and their association with mental health problems. Participants: We assessed a sample of 373 institutionalized children (45.8 % male) with a mean age of 9.44 years (range: 6–13) from 24 registered and unregistered childcare institutions in Dar es Salaam region, Tanzania. Methods: Structured interviews were conducted assessing current maltreatment by caregivers and peer victimization in the orphanage, previous maltreatment in the family of origin, and mental health problems. Results: Almost all children experienced maltreatment by different perpetrators (caregivers, peers, family of origin). About one-fifth of all children reported mental health problems. Maltreatment by caregivers (β = 0.14) and peer violence (β = 0.18) were significantly associated with mental health problems. In a second model including only children reporting on the family of origin, maltreatment in the family of origin (β = 0.24) and peer violence (β = 0.16) were significantly associated with mental health problems. Conclusion: In addition to maltreatment in the family of origin, OVC reported experiences of maltreatment both by caregivers and peers in the orphanage. The prevalence of maltreatment and its association with mental health problems underline the urgent need for prevention of maltreatment in institutional care in Tanzania.